Development of Multimedia-Based Worksheets as a Teaching Material on Sub-Material of Invertebrates - Titin, Titin; Panjaitan, Ruqiah Ganda Putri; Widiyatmoko, Arif (Jurnal Penelitian dan Pembelajaran IPA, 2022)
The purpose of this study is to develop multimedia- based student worksheets in invertebrates sub materials and to describe both the response and scoring result of tenth grade students in Pontianak who learn to use the instructional materials. This research method is Research and Development. The development steps carried out are: 1) potential and problems, 2) information gathering, 3) product design, 4) design validation, 5) product design improvement and 6) product testing. In the product trial phase, a sample of 208 students was used. The validation from both material and media experts on multimedia- based student worksheets in invertebrate sub- materials was confirmed as valid. The student responses at schools with KTSP and curriculum 2013 on the use of multimedia- based student worksheets in Invertebrates sub material were in the fair positive and positive category. The average values obtained by students in schools that applied the KTSP and 2013 curriculum were 40.08 and 54.16 respectively. It was concluded that multimedia-based worksheets were appropriate to be used as teaching material in invertebrates sub material.